Efecto antimicrobiano in vitro de la Camellia sinensis sobre bacterias orales - Moromi Nakata, Hilda (2007)
In order to determine, the antimicrobial effect in vitro of solutions of Camellia sinensis (green tea) of four commercial products (A, B, C and D), we recolected not stimulated saliva of 40 university students and cultivated them in Tripticase soy Agar using Assay disc diffusion for the tea solutions, (Amoxilicina) as a positive control group and (distilled water) as a negative control group, plates were incubated to 37 °C/24 hours. The same procedure was performed for S. mutans ATCC 25175. According to results, all commercial products of green tea produced inhibition of zones of growth colonies. The statistical analysis of four commercial products of tea determined that significant differences between medias of the samples exists. Comparing couples of medias, it shows the existence of significant differences to level of 0.05 between couples of marks AB; AC; BD; CD. The analysis of samples of green tea infusion determined the presence of polyphenols, by espectrophotometry-infrared with transformed of Fourier (FT - IR), observed peaks of transmittance in wave lengths for the oxidriles groups (-0H) and aromatic ring. It is concluded that the antibacterial action has been demonstrated for the S. mutans, and for mixed salivary microflora, and there are differences in the action, depending on the product used. It is necessary to continue with studies to verify antimicrobial effect in vivo, to use as mouthrinse, as well as studies to analyze the principal active components of green tea to identify the best solutions to use for that purpose, studies of cost/ benefit, acceptability between users, effect on other microorganisms, etc.